2021
DOI: 10.1088/2051-672x/ac1dc3
|View full text |Cite|
|
Sign up to set email alerts
|

Multifractal analysis of high-temperature plasma irradiated tungsten surfaces

Abstract: In this research, the irregular surface structure of 15 pure tungsten specimens that are irradiated respectively with 20, 40, 60, 80, and 100 shots of high-temperature deuterium plasma are under observation. The box-counting method is used to evaluate the scanning electron microscope (SEM) images taken from different locations within the same specimen. Obtained multifractal characteristics are then compared with the Fourier spectrum of stochastic relief. As a result, it is possible to determine the time depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…With respect to monofractals and non-fractals, the graph D(q) vs q has a small variance, while for multifractals, D(q) usually decreases with a decrease in q, which often occurs sigmoidally before the point q = 0. Details of the application of the MF theory and the box-counting method can be found in the articles of previous studies [36,37].…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to monofractals and non-fractals, the graph D(q) vs q has a small variance, while for multifractals, D(q) usually decreases with a decrease in q, which often occurs sigmoidally before the point q = 0. Details of the application of the MF theory and the box-counting method can be found in the articles of previous studies [36,37].…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…from plasma-irradiated surfaces. By using the concept of multifractals, in addition to the usual descriptive methods [20], quantitative values and graphs characterizing the surface damage structures as a whole can be studied [22,[36][37][38]. The box-counting technique can be applied to surfaces of a defected material as well as to the same surfaces of non-defects (without a defected area).…”
Section: Introductionmentioning
confidence: 99%
“…Butenko et al [14] carried out a multifractal analysis on nitinol glass annealed at different temperatures, counted its surface characteristics, and verified the possibility of detecting system phase transition in crystalline form. Martsepp et al [15] irradiated pure tungsten samples with high-temperature deuterium plasma at different times and compared the multifractal spectrum of the sample surface with the Fourier spectrum. The multifractal spectrum of the surface can determine the time dependence of surface damage.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, different methods of fractal analysis have been successfully used to decode the surface finishing in engineering ceramics and sapphire single crystals [17,20]. In addition, various studies revealed that the 3D surface microtexture can be described using stereometric [21][22][23], and fractal/multifractal analyses [24][25][26][27][28] with a minimal set of surface parameters.…”
Section: Introductionmentioning
confidence: 99%